Catalyst-free reductions of nitriles to amino-boranes using sodium amidoborane and lithium borohydride. Issue 6 (27th January 2022) - Peng, Jiamin; Song, Yuwei; Wang, Yingying; Liu, Zhenxing; Chen, Xuenian
Abstract : The combination of sodium amidoborane (NaAB) and lithium borohydride (LiBH4 ) (mixed at a 1 : 3 molar ratio) can efficiently reduce various nitriles into amine-boranes at room temperature without catalysts. Abstract : An efficient and facile method to reduce nitriles to amine-boranes was developed. Aromatic and aliphatic nitriles were readily reduced in the presence of both sodium amidoborane (NaAB) and LiBH4 at room temperature in THF without catalysts, affording products in up to 99% yield. The products can be easily hydrolyzed to afford primary amines or utilized as reducing reagents for one-pot reductive amination. The key finding of the reaction study is the synergy effect between NaAB and LiBH4 ; otherwise the reaction yield would drop substantially from 92% to 22% or 12% when NaAB and LiBH4 are used separately.